Analysis of Heart Rate Variability and Anaerobic Performance in Female Athletes Based on Menstrual Cycle Phases - Naufal Abdul Aziz; Muhamad Lutfanpadil; Rezky Okta Dwi Ramadhan; M. Arief Setiawan; A. Ine Aprilia Damai; Aprillia Wulan Utari (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
Female athletes’ participation in competitive sports requires a comprehensive understanding of specific physiological factors, including hormonal fluctuations during the menstrual cycle that may affect physical performance and injury risk. This study aimed to analyze the effects of menstrual cycle phases on cardiovascular endurance, explosive strength, and neuromuscular stability in female athletes. The study employed a quantitative approach with a quasi-experimental design using a repeated measures design on the same subjects across three menstrual cycle phases: menstruation, ovulation, and luteal phases. Samples were selected purposively based on specific criteria. Measurements were conducted using the Multi-Stage Fitness Test for VO₂max, the Vertical Jump Test for explosive strength, as well as the Y-Balance Test and knee valgus analysis for neuromuscular stability. Data were analyzed using Repeated Measures ANOVA and Bonferroni post hoc tests. The results showed significant differences (p < 0.05) in all variables across cycle phases. The ovulation phase demonstrated the highest performance in VO₂max and explosive strength, which was associated with increased estrogen levels. However, this phase also showed decreased neuromuscular stability and increased knee valgus angle, indicating a higher risk of injury. In contrast, the menstruation phase showed the lowest performance, while the luteal phase experienced declines in both performance and stability. The discussion confirmed a trade-off between improved performance and increased injury risk during ovulation due to hormonal influences on the neuromuscular system and connective tissues. Therefore, the conclusion of this study emphasizes the importance of implementing menstrual cycle-based training periodization to optimize performance while minimizing injury risk in female athletes.